Towards a Macromarketing and Consumer Culture Theory Intersection: Participatory and Deliberative Methodologies. (March 2019) - Saatcioglu, Bige; Corus, Canan
This article provides a discussion on the use of an alternative paradigm towards a cross-fertilization of CCT and macromarketing. Researchers at the intersection of CCT and macromarketing can benefit from both research traditions' relative strength: the deep sociocultural focus of CCT and the structural lens of Macromarketing. To facilitate this dialogue, the authors propose an innovative and inclusive approach to research design and data collection. More specifically, the action research paradigm that is driven by an agenda for an egalitarian participation into the social sphere, a multidimensional wellbeing, and a reflexive social change is introduced. The discussion on an action research-driven research design and methodology also builds upon the key insights of Macromarketing and CCT traditions and offers a detailed framework for researchers who wish to bring an alternative and fresh look into a CCT/Macromarketing alliance.